HYBRID SUBJECT NEGOTIATION OVER CONFLICTING EASTERN AND WESTERN CULTURAL VALUES IN THE FAREWELL (2019) - Silvia Valentina Putri; Hujuala Rika Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Colonialism has created a binary identity division between "West" and "East," which has given rise to a dynamic conflict between Western and Eastern cultural values. The Farewell (2019) reveals the conflict between the West with its individualism and the East with its collectivism. This study uses a textual analysis method to examine the identity negotiations of the main characters in the conflict of cultural values. As a tool for analytical reading, this study employs Homi K. Bhabha’s hybridity based on postcolonial theory. In the film, hybridity is reflected in Billi, a Chinese-American woman who lives between two cultural values. Billi's identity is not only formed by one culture; Billi can be more American in one context and more Chinese in another. As a hybrid subject, Billi will continuously reshape her identity. In dealing with the situation, Billi makes compromises. In Billi's case, the negotiation process isn't simply about finding a final, one-sided answer. Rather, it's about the ongoing process of identity formation.